Performance Of Milkfish (Chanos chanos) Cultured by Different Stocking Density in Floating Net Cages Lake Batur, Trunyan Village, Bali - Sukmawantara, Gede Dwi; Arthana, I Wayan; Kartika, Gde Angga Raka (Advances in Tropical Biodiversity and Environmental Sciences; Vol 5 No 1 (2021): ATBES, 2021)
Lake Batur is the largest lake in the island of Bali. Lake Batur is widely used by the community in the aquaculture sector, namely floating net cage cultivation. The research aims to determine the influence of different stocking density on the growth rate and survival rate of the milkfish ( Chanos chanos ) in the 4 x 1 meters floating net cages in Lake Batur, Trunyan village. Data collection was done every two weeks during two months observation, from January 2020 – March 2020. The research used a complete random design consisting of three treatments and three replications of each treatment, which the treatment A of 15 fish/0.25m 3 , treatment B of 20 fish/0.25m 3 , and the treatment C of 25 fish/0.25m 3 . Measurements of fish length, fish weight, and water quality were done in situ. The results showed that the difference in stocking density had no effect on the absolute length, but those difference had an effect on the specific growth rate (SGR) and the survival rate of the fish. Treatment B resulted a maximum value of the growth rate, with an absolute length value of 0.69 ± 0.115cm/2 month and SGR 1.02 ± 0.095%/day. The fish survival rate at treatment A resulted in the highest value of 89 ± 3.46%/2 month. The value of water quality during the study were temperature of 25.9 ± 0.8 o C, DO of 8.3 ± 0,1 mg/L, pH of 9.4 ± 0.2, and TDS of 995.5 ± 70.8 ppm.